Work-in-Progress: Towards a First Biological Realization of Thermomolecular Communications - Ntetsikas, Nikolaos; Gattringer, Michael; Angerbauer, Stefan; Lestas, Marios; Haselmayr, Werner (My University, 2024)
This work-in-progress paper introduces a novel concept for the practical realization of a first biological thermomolecular communications testbed using eukaryotic yeast cells as receiver. In particular, we sketch the idea of the testbed and present the theoretical basics.
Keywords: Gateway; Thermomolecular Communications; IoBNT; Molecular Communications; Yeast; Testbed